Positioning holes on tubes to optimise energy absorption - Chia, Alex Jiajun. (2012)
Steel is one of the most cost-effective choices of material for structural functions. The shell of automobiles mainly serves as a barrier to shield the interior from external weather, and also operates to improve the aerodynamics of the vehicle. In the aspect of aerodynamics, the fuel efficiency is often the attribute that appears along with it. Hence, reducing the quantity of steel will be beneficial to the fuel efficiency. Since the crumple zones of cars have the purpose of providing protection through controlled deformation, in the event of a crash accident. It is ideal that introducing intended holes onto the structural framework can reduce the overall mass, while not hampering the original energy absorption in the crumple zone. Therefore, this project is designed to explore the effects of the various positioning of holes, and to attain an optimum configuration that can also maximise the energy absorption potential.